Pengaruh Motivasi Kerja Kepuasan Kerja Disiplin Kerja Pegawai PT PELINDO INDONESIA - Rahmatillah, Alvin; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study examines the impact of Brand Trust, Brand Image, Brand Awareness, and Hedonic his study aims to determine and analyze the influence of work motivation, job satisfaction, and work discipline on employee performance at PT Pelindo Indonesia. The background of this study is based on the phenomenon of fluctuating employee performance that has an impact on company productivity. Employee performance is influenced by various internal and external factors, including motivation, satisfaction, and work discipline. This study uses a quantitative approach with data collection techniques through questionnaires distributed to 62 employees at the PT Pelindo Indonesia Surabaya Office. The data analysis technique uses multiple linear regression with the help of SPSS software version 26. The results of the study indicate that the variables of work motivation, job satisfaction, and work discipline simultaneously have a positive and significant effect on employee performance. Partially, the three variables also each have a positive and significant effect on employee performance. This means that the higher the level of employee motivation, satisfaction, and discipline, the better the performance displayed by the employee. This finding strengthens previous research which states that these factors have a close relationship with increased performance in the work environment. This study provides practical implications for the management of PT Pelindo Indonesia in formulating policies to improve employee performance through providing appropriate motivation, creating a work environment that supports job satisfaction, and implementing consistent work discipline. This study also contributes to the development of human resource management theory in the BUMN service sector. Keywords: Work Motivation, Job Satisfaction, Work Discipline, Employee Performance, PT Pelindo Indonesia.